Waterproof and breathable coating for leather and preparation method of waterproof and breathable coating

By introducing silicone modified acrylate copolymer and functional nanofiller into the waterproof and breathable glue for the leather, combined with specific formula ratios and preparation methods, the problem of degradation of traditional coatings under extreme cold conditions is solved, and the stable performance in extremely cold environments and the effect of extending service life is achieved.

CN119799142AInactive Publication Date: 2025-04-11SHENZHEN JINHONGMAO ADHESIVE PRODUCTS CO LTD

Patent Information

Application Number
CN202510091537.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing waterproof and breathable coating for leather materials shows deterioration in flexibility, wear resistance and waterproof and breathable properties under extreme cold conditions, limiting its application range and affecting the quality and service life of leather products.

Method used

A waterproof and breathable glue is used for leather materials containing polyurethane resin, silicone modified acrylate copolymer, fluorocarbon surfactant, antifreeze, film forming additive, plasticizer, functional nanofiller, crosslinking agent, dispersant and pH adjuster. Through specific formula ratios and preparation methods, stable physical and chemical properties are maintained under extreme cold conditions.

Benefits of technology

The leather material is made of waterproof and breathable paste glue to maintain good flexibility and mechanical strength under extremely cold conditions, ensuring that the waterproof and breathable performance of the coating does not weaken, extending the service life of leather products and expanding its scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799142A_ABST
    Figure CN119799142A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of leather treatment, and particularly relates to a waterproof breathable coating for leather and a preparation method thereof.According to the waterproof breathable coating for the leather and the preparation method thereof, siloxane modified acrylate copolymer and functional nano filler are introduced, good flexibility and mechanical strength can still be kept in a low-temperature environment, and it is ensured that a coating cannot become brittle or crack due to temperature reduction; besides, the freezing point of the system is effectively reduced due to the existence of the anti-freezing agent, the material is prevented from being frozen at a low temperature, and meanwhile, good film-forming property and softness of the coating under a low-temperature condition are ensured due to the combined action of the coalescing agent and the plasticizer; finally, the waterproof and breathable laminated glue for the leather provided by the invention not only can provide excellent waterproof and breathable properties at normal temperature, but also can maintain stable physicochemical properties under extremely cold conditions, so that the service life of a leather product is greatly prolonged, and the application range of the leather product is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of leather processing, and particularly relates to a waterproof and breathable laminating agent for leather and a preparation method thereof. Background Art

[0002] In leather products, in order to improve their durability and functionality, a waterproof and breathable coating is usually applied to the leather surface. Existing waterproof and breathable coatings are mainly composed of materials such as polyurethane resins and acrylate copolymers. These materials can provide a certain degree of waterproofness and breathability to meet the use requirements under normal conditions. However, in extremely cold weather conditions (for example, temperatures below -10°C), traditional waterproof and breathable layers may fail. The main reasons include:

[0003] Material properties: Some waterproof and breathable coatings will become stiff at low temperatures, affecting their elasticity and sealing, resulting in reduced waterproof performance.

[0004] Curing process: If the glue is cured under inappropriate temperature conditions, it may not form an ideal molecular structure to maintain long-term waterproof and breathable effects.

[0005] Environmental factors: Extremely cold environments may cause moisture to condense into ice crystals, destroying the microporous structure of the coating and affecting breathability.

[0006] The waterproof and breathable coating for leather in the prior art has a significant performance degradation problem in low temperature environments, especially in extremely cold conditions. The flexibility, wear resistance and waterproof and breathable properties of the coating cannot be guaranteed, which limits its application scope in cold areas and affects the overall quality and service life of leather products. Summary of the invention

[0007] The purpose of the present invention is to provide a waterproof and breathable lamination for leather and a preparation method thereof, which can not only provide excellent waterproof and breathable performance at room temperature, but also maintain stable physical and chemical properties under extremely cold conditions, greatly extending the service life of leather products and improving their scope of application, so as to solve the problems raised in the above-mentioned background technology.

[0008] To achieve the above object, the present invention provides a waterproof and breathable laminating material for leather, wherein the waterproof and breathable laminating material for leather comprises the following components in percentage by weight:

[0009] Polyurethane resin: 25-30%; siloxane modified acrylate copolymer: 15-20%; fluorocarbon surfactant: 5-8%; antifreeze: 4-6%; film-forming aid: 3-5%; plasticizer: 3-5%; functional nanofiller: 2-4%; cross-linking agent: 1-2%; dispersant: 0.5-1%; pH adjuster: 0.1-0.5%; solvent: the remainder to 100%.

[0010] Preferably, the silicone-modified acrylate copolymer comprises the following ingredients:

[0011] Acrylate monomer: one or more selected from methyl acrylate, ethyl acrylate, and butyl acrylate;

[0012] Siloxane functional group-containing monomer: one or more selected from vinyl trimethoxy silane, vinyl triethoxy silane, and methacryloxypropyl trimethoxy silane;

[0013] Cross-linking agent: one or more selected from hexylene glycol diacrylate and trimethylolpropane triacrylate;

[0014] Initiator: one or more selected from dibenzoyl peroxide and azobisisobutyronitrile.

[0015] Preferably, the film-forming aid comprises the following ingredients:

[0016] Phthalate esters: one or more selected from dibutyl phthalate and dioctyl phthalate;

[0017] Alcohol esters: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate;

[0018] Polyol ethers: one or more selected from ethylene glycol monobutyl ether and propylene glycol monomethyl ether.

[0019] Preferably, the plasticizer comprises the following ingredients:

[0020] Phthalate esters: one or more selected from dioctyl phthalate and dibutyl phthalate;

[0021] Aliphatic dibasic acid esters: one or more of dioctyl adipate and dioctyl sebacate.

[0022] Preferably, the functional nanofiller comprises the following ingredients:

[0023] Silica nanoparticles: average particle size is 10-50 nanometers;

[0024] Alumina nanoparticles: average particle size is 20-80 nanometers;

[0025] Titanium dioxide nanoparticles: average particle size is 15-40 nanometers;

[0026] Montmorillonite nanoclay: The average particle size is 30-100 nanometers.

[0027] Carbon nanotubes: The average diameter is 1-10 nanometers.

[0028] Preferably, the cross-linking agent comprises the following components:

[0029] Aziridine compounds: one or more selected from 1,2-epoxy-3-(2-methoxyethoxy)propane and 1,2,7,8-diepoxyoctane;

[0030] Isocyanate compound: one or more selected from hexamethylene diisocyanate and isophorone diisocyanate;

[0031] Metal chelate: one or more selected from tetra-n-butyl titanate and tetra-n-butyl zirconate.

[0032] Preferably, the dispersant comprises the following ingredients:

[0033] Polyphosphates: one or more selected from sodium hexametaphosphate and sodium tripolyphosphate;

[0034] Acrylic polymer: one or more selected from sodium polyacrylate and polymethacrylic acid.

[0035] On the other hand, the present invention provides a method for preparing a waterproof and breathable lamination for leather, comprising the following steps:

[0036] Raw material preparation: accurately weigh each component according to the weight percentage of the raw material for waterproof and breathable lamination of leather;

[0037] Mixing and dispersion: add polyurethane resin, silicone modified acrylate copolymer, fluorocarbon surfactant and solvent into a high-speed disperser, and stir at a speed of 1000-1500 rpm for 30-60 minutes at a temperature of 25-35°C;

[0038] Adding functional ingredients: under continuous stirring, slowly adding antifreeze agent, film-forming aid, plasticizer, functional nanofiller, crosslinking agent and dispersant in sequence, and continuing to stir for 15-30 minutes after each ingredient is added to obtain a mixture;

[0039] Vacuum degassing: the mixture is transferred to a vacuum degassing device and treated at a pressure of -0.09 MPa to -0.1 MPa for 10-20 minutes to remove bubbles;

[0040] Filtration and packaging: Use multi-stage filtration screens to remove large particles that are not fully dispersed, and then sterile packaging is performed to obtain the final product.

[0041] Preferably, in the mixing and dispersing, a high-speed disperser with heating and cooling functions is used to control the reaction temperature, and the temperature fluctuation is kept within ±2° C. during the stirring process.

[0042] Preferably, a pH adjuster is added to the added functional ingredients to maintain the pH value between 7.0-8.5.

[0043] Technical effects and advantages of the present invention: The waterproof and breathable laminating material for leather and the preparation method thereof provided by the present invention have the following advantages compared with the prior art:

[0044] The present invention can maintain good flexibility and mechanical strength in a low-temperature environment by introducing a siloxane-modified acrylate copolymer and a functional nanofiller, thereby ensuring that the coating will not become brittle or crack due to a decrease in temperature; in addition, the presence of the antifreeze agent effectively lowers the freezing point of the system to prevent the material from freezing at low temperatures, while the film-forming aid and the plasticizer work together to ensure good film-forming properties and softness of the coating under low-temperature conditions; finally, the waterproof and breathable lamination for leather provided by the present invention can not only provide excellent waterproof and breathable performance at room temperature, but also maintain stable physical and chemical properties under extremely cold conditions, thereby greatly extending the service life of leather products and improving their scope of application. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention is a flow chart of a method for preparing a waterproof and breathable lamination for leather. DETAILED DESCRIPTION

[0046] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] The present invention provides a waterproof and breathable laminating agent for leather, which can maintain good flexibility and mechanical strength in a low-temperature environment by introducing a siloxane-modified acrylate copolymer and a functional nanofiller, ensuring that the coating will not become brittle or crack due to temperature reduction; in addition, the presence of an antifreeze agent effectively reduces the freezing point of the system to prevent the material from freezing at low temperatures, and at the same time, the film-forming aid and the plasticizer work together to ensure good film-forming properties and softness of the coating under low-temperature conditions;

[0049] The waterproof and breathable laminating material for leather comprises the following components in percentage by weight:

[0050] Polyurethane resin: 25-30%; siloxane modified acrylate copolymer: 15-20%; fluorocarbon surfactant: 5-8%; antifreeze agent: 4-6%; film-forming aid: 3-5%; plasticizer: 3-5%; functional nanofiller: 2-4%; cross-linking agent: 1-2%; dispersant: 0.5-1%; pH adjuster (ammonia water): 0.1-0.5%; solvent (water): balance to 100%.

[0051] In one embodiment, the silicone-modified acrylate copolymer comprises the following ingredients:

[0052] Acrylate monomer: one or more selected from methyl acrylate, ethyl acrylate, and butyl acrylate; these monomers endow the copolymer with good film-forming properties and excellent adhesion to substrates (such as leather). In particular, butyl acrylate, due to its longer side chain structure, can provide higher flexibility, making the coating less likely to become brittle at low temperatures.

[0053] Monomers containing siloxane functional groups: selected from one or more of vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane; the introduction of siloxane segments not only reduces the surface energy of the coating, improves hydrophobicity, but also enhances the material's weather resistance and UV resistance. The siloxane part can form a more stable network structure between molecules, ensuring that the waterproof performance does not decay during long-term use.

[0054] Crosslinking agent: One or more of hexylene glycol diacrylate and trimethylolpropane triacrylate are selected; these multifunctional monomers promote the crosslinking reaction between polymer chains, forming a stronger and more stable three-dimensional network structure. This not only improves the mechanical strength of the coating, but also enhances its wear resistance and tear resistance, especially under extreme environmental conditions.

[0055] Initiator: one or more selected from dibenzoyl peroxide and azobisisobutyronitrile. These initiators can effectively start the free radical polymerization reaction and control the polymerization rate, ensuring that the components are evenly dispersed throughout the preparation process, and the final product has good construction performance and appearance quality.

[0056] In one embodiment, the film-forming aid comprises the following ingredients:

[0057] Phthalate esters: one or more selected from dibutyl phthalate and dioctyl phthalate;

[0058] Alcohol esters: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate;

[0059] Polyol ethers: one or more selected from ethylene glycol monobutyl ether and propylene glycol monomethyl ether.

[0060] The above film-forming agent combination can ensure that a uniform, continuous waterproof and breathable layer with good physical properties can be formed in a low-temperature environment, which is particularly suitable for treating substrates such as leather that have high requirements for flexibility. In addition, by optimizing the ratio of each component, the drying speed, hardness and surface texture of the final product can be further adjusted to meet different application requirements.

[0061] In one embodiment, the plasticizer comprises the following ingredients:

[0062] Phthalate esters: one or more selected from dioctyl phthalate and dibutyl phthalate;

[0063] Aliphatic dibasic acid esters: one or more of dioctyl adipate and dioctyl sebacate.

[0064] The above plasticizer combination can significantly improve the flexibility and elasticity of the waterproof and breathable layer, ensure that it can still maintain good mechanical properties under low temperature conditions, and prevent the coating from becoming brittle or cracking. In addition, by optimizing the proportion of each component, the feel, abrasion resistance and tear strength of the final product can be adjusted according to specific application requirements to meet the requirements of different leather products.

[0065] In one embodiment, the functional nanofiller comprises the following ingredients:

[0066] Silica nanoparticles: average particle size is 10-50 nanometers;

[0067] Alumina nanoparticles: average particle size is 20-80 nanometers;

[0068] Titanium dioxide nanoparticles: average particle size is 15-40 nanometers;

[0069] Montmorillonite nanoclay: The average particle size is 30-100 nanometers.

[0070] Carbon nanotubes: The average diameter is 1-10 nanometers.

[0071] The above functional nanofiller combination can significantly improve the overall performance of the waterproof and breathable layer, ensuring that it can maintain good mechanical strength, wear resistance and breathability under low temperature conditions. In addition, by optimizing the proportion of each component, the physical and chemical properties of the final product, such as hardness, flexibility, moisture permeability and UV resistance, can be adjusted according to specific application requirements to meet the requirements of different leather products.

[0072] In one embodiment, the cross-linking agent comprises the following components:

[0073] Aziridine compounds: one or more selected from 1,2-epoxy-3-(2-methoxyethoxy)propane and 1,2,7,8-diepoxyoctane;

[0074] Isocyanate compound: one or more selected from hexamethylene diisocyanate and isophorone diisocyanate;

[0075] Metal chelate: one or more selected from tetra-n-butyl titanate and tetra-n-butyl zirconate.

[0076] The above cross-linking agent combination can significantly enhance the internal structural stability of the waterproof and breathable layer, ensuring that good physical properties can be maintained in low temperature environments. In addition, by optimizing the ratio of each component, the curing speed, hardness and flexibility of the final product can be adjusted according to specific application requirements to meet the requirements of different leather products.

[0077] In one embodiment, the dispersant comprises the following ingredients:

[0078] Polyphosphates: one or more selected from sodium hexametaphosphate and sodium tripolyphosphate;

[0079] Acrylic polymer: one or more selected from sodium polyacrylate and polymethacrylic acid.

[0080] The above dispersant combination can significantly improve the dispersion effect of various solid components in the waterproof and breathable layer, ensuring the long-term stability and construction performance of the coating system. In addition, by optimizing the ratio of each component, the viscosity, fluidity and thixotropy of the final product can be adjusted according to specific application requirements to meet the requirements of different leather products.

[0081] The preparation method of the above leather material with waterproof and breathable lamination, as Figure 1 As shown, the following steps are included:

[0082] Raw material preparation: accurately weigh each component according to the weight percentage of the raw material for waterproof and breathable lamination of leather;

[0083] Mixing and dispersion: add polyurethane resin, silicone modified acrylate copolymer, fluorocarbon surfactant and solvent into a high-speed disperser, and stir at a speed of 1000-1500 rpm for 30-60 minutes at a temperature of 25-35°C;

[0084] Adding functional ingredients: under continuous stirring, slowly adding antifreeze agent, film-forming aid, plasticizer, functional nanofiller, crosslinking agent and dispersant in sequence, and continuing to stir for 15-30 minutes after each ingredient is added to obtain a mixture;

[0085] Vacuum degassing: the mixture is transferred to a vacuum degassing device and treated at a pressure of -0.09 MPa to -0.1 MPa for 10-20 minutes to remove bubbles;

[0086] Filtration and packaging: Use multi-stage filtration screens to remove large particles that are not fully dispersed, and then sterile packaging is performed to obtain the final product.

[0087] In one embodiment, during the mixing and dispersing, a high-speed disperser with heating and cooling functions is used to control the reaction temperature and keep the temperature fluctuation within ±2° C. during the stirring process.

[0088] In one embodiment, a pH adjuster is added to the added functional ingredients to maintain the pH value between 7.0-8.5.

[0089] Example 2: Optimized formula and performance test of waterproof and breathable lamination for leather

[0090] Based on the basic formula and preparation method provided in Example 1, this example aims to further optimize the performance of waterproof and breathable lamination for leather by adjusting the proportion of certain ingredients and introducing new functional nanofillers, especially improving its flexibility and wear resistance in extremely cold environments. At the same time, a series of experiments were conducted to verify whether the improved formula achieved the expected effect.

[0091] Recipe Adjustment:

[0092] While keeping other ingredients unchanged, the following ingredients were adjusted:

[0093] Siloxane modified acrylate copolymer: increased to 20% (originally 15-20%, take the upper limit);

[0094] Antifreeze: increased to 6% (originally 4-6%, take the upper limit);

[0095] Functional nanofillers: New carbon nanotubes (CNTs) were introduced with an average diameter of 5 nanometers and an addition amount of 0.3% of the total weight;

[0096] Preparation method:

[0097] The steps in Example 1 were followed for raw material preparation, mixing and dispersing, adding functional ingredients, vacuum degassing, and filtering and packaging. In particular, a high-speed disperser with heating and cooling functions was used during the mixing and dispersing stage to ensure that the temperature was controlled at 28°C, and the stirring speed was set to 1200 rpm for 45 minutes. When adding functional ingredients, each ingredient was stirred for 20 minutes after addition to ensure that it was fully mixed.

[0098] Performance Testing:

[0099] In order to evaluate the performance of the improved formulation, the following tests were conducted:

[0100] Low temperature flexibility test:

[0101] Test conditions: Bending test was performed after being placed at -20℃ for 24 hours.

[0102] Results: The treated leather samples showed no cracking or peeling after being folded repeatedly 100 times, indicating that the coating had good low-temperature flexibility.

[0103] Abrasion resistance test:

[0104] Test conditions: A standard wear tester was used at room temperature with constant pressure (500 g) and fixed number of frictions (10,000 times).

[0105] Results: Compared with Example 1, the improved coating showed higher wear resistance and the wear index decreased by about 20%, indicating that the coating was more durable.

[0106] Waterproof test:

[0107] Test conditions: The water contact angle measurement method was used to test the contact angle of water droplets on the coating surface at room temperature and low temperature (-10°C).

[0108] Results: The contact angle was 110°±5° at room temperature and 105°±5° at low temperature, indicating that the coating still maintained excellent waterproof properties even in low temperature environments.

[0109] Air permeability test:

[0110] Test conditions: Use an air permeability tester to measure the gas permeability per unit area at a relative humidity of 90% and a temperature of 23°C.

[0111] Results: The air permeability was increased by about 15% compared with Example 1. This was due to the application of the new nanofiller, which made the microporous structure inside the coating more uniform and promoted gas exchange.

[0112] Experimental data summary

[0113]

[0114] The above experimental data show that by adjusting the formula ratio and introducing the new nanofiller, the performance of the waterproof and breathable laminating agent for leather in Example 2 is improved in all aspects, especially in terms of flexibility and wear resistance in low temperature environments. This not only proves the effectiveness of the new formula, but also provides stronger technical support for practical applications.

[0115] Example 3: Further optimization of waterproof and breathable lamination for leather and its performance verification

[0116] Based on Example 1 and Example 2, this example aims to further improve the comprehensive performance of waterproof and breathable lamination for leather by introducing additional functional ingredients and fine-tuning the preparation process. In particular, the durability and UV resistance of the coating in extreme environments are improved. In addition, the performance of the new formula in practical applications will also be tested.

[0117] Recipe Adjustment:

[0118] Based on the successful experience of Example 2, the following components were further adjusted and added in this example:

[0119] Siloxane-modified acrylate copolymer: maintained at 20% (same as Example 2);

[0120] Antifreeze: maintained at 6% (same as in Example 2);

[0121] Functional nanofillers: Carbon nanotubes (CNTs) with an average diameter of 5 nanometers are retained and added at 0.3% of the total weight. Titanium dioxide (TiO2) nanoparticles with an average particle size of 20 nanometers are introduced at 0.5% of the total weight to enhance UV resistance.

[0122] Environmentally friendly plasticizer: acetyl tributyl citrate (ATBC) is introduced to replace part of the phthalate plasticizers, with the addition amount being 1.5% of the total weight to improve environmental protection and biodegradability.

[0123] Light stabilizer: An appropriate amount of hindered amine light stabilizer (HALS), such as bis(1,2,2,6,6-pentamethylpiperidin-4-yl) sebacate, is added at 0.2% of the total weight to enhance the weather resistance of the coating.

[0124] Preparation method:

[0125] The steps in Example 1 and Example 2 were followed for raw material preparation, mixing and dispersing, adding functional ingredients, vacuum degassing, and filtering and packaging. In particular, a high-speed disperser with heating and cooling functions was used during the mixing and dispersing stage to ensure that the temperature was controlled at 30°C, and the stirring speed was set to 1300 rpm for 50 minutes. When adding functional ingredients, each ingredient was stirred for 25 minutes after addition to ensure that it was fully mixed.

[0126] Performance Test:

[0127] In order to evaluate the performance of the improved formulation, the following tests were conducted:

[0128] Low temperature flexibility test:

[0129] Test conditions: Bending test was performed after being placed at -30℃ for 48 hours.

[0130] Results: The treated leather samples showed no cracking or peeling after being folded 200 times, indicating that the coating had excellent low-temperature flexibility.

[0131] Abrasion resistance test:

[0132] Test conditions: A standard wear tester was used at room temperature with constant pressure (750 g) and fixed number of frictions (15,000 times).

[0133] Results: Compared with Example 2, the improved coating showed higher wear resistance and the wear index decreased by about 30%, indicating that the coating was more durable.

[0134] Waterproof test:

[0135] Test conditions: The water contact angle measurement method was used to test the contact angle of water droplets on the coating surface at room temperature and low temperature (-15°C).

[0136] Results: The contact angle was 115°±5° at room temperature and 110°±5° at low temperature, indicating that the coating still maintained excellent waterproof properties even in lower temperature environments.

[0137] Air permeability test:

[0138] Test conditions: Use an air permeability tester to measure the gas permeability per unit area at a relative humidity of 90% and a temperature of 23°C.

[0139] Results: The air permeability was increased by about 10% compared with Example 2. This was due to the application of the new nanofiller, which made the microporous structure inside the coating more uniform and promoted gas exchange.

[0140] UV resistance test:

[0141] Test conditions: Use an accelerated aging test chamber to simulate natural light conditions, with a cumulative exposure time of 1,000 hours.

[0142] Results: After testing, the color change of the coating was minimal, and the color difference ΔE value was less than 1.5, proving that it has good UV resistance.

[0143] Experimental data summary:

[0144]

[0145]

[0146] The above experimental data show that by introducing the new nanofiller and light stabilizer, the performance of the waterproof and breathable lamination for leather in Example 3 is improved in all aspects, especially in terms of flexibility and wear resistance in low temperature environment, and excellent anti-ultraviolet performance is added. This not only proves the effectiveness of the new formula, but also provides stronger technical support for practical applications.

[0147] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A waterproof and breathable laminating material for leather, characterized in that: The waterproof and breathable laminating material for leather comprises the following components in percentage by weight: Polyurethane resin: 25-30%; Silicone modified acrylate copolymer: 15-20%; Fluorocarbon surfactant: 5-8%; Antifreeze: 4-6%; Film-forming aid: 3-5%; Plasticizer: 3-5%; Functional nanofillers: 2-4%; Cross-linking agent: 1-2%; Dispersant: 0.5-1%; pH adjuster: 0.1-0.5%; Solvent: Balance to 100%.

2. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The silicone-modified acrylate copolymer comprises the following ingredients: Acrylate monomer: one or more selected from methyl acrylate, ethyl acrylate, and butyl acrylate; Siloxane functional group-containing monomer: one or more selected from vinyl trimethoxy silane, vinyl triethoxy silane, and methacryloxypropyl trimethoxy silane; Cross-linking agent: one or more selected from hexylene glycol diacrylate and trimethylolpropane triacrylate; Initiator: one or more selected from dibenzoyl peroxide and azobisisobutyronitrile.

3. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The film-forming aid comprises the following ingredients: Phthalate esters: one or more selected from dibutyl phthalate and dioctyl phthalate; Alcohol esters: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate; Polyol ethers: one or more selected from ethylene glycol monobutyl ether and propylene glycol monomethyl ether.

4. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The plasticizer comprises the following ingredients: Phthalate esters: one or more selected from dioctyl phthalate and dibutyl phthalate; Aliphatic dibasic acid esters: one or more of dioctyl adipate and dioctyl sebacate.

5. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The functional nanofiller comprises the following ingredients: Silica nanoparticles: average particle size is 10-50 nanometers; Alumina nanoparticles: average particle size is 20-80 nanometers; Titanium dioxide nanoparticles: average particle size is 15-40 nanometers; Montmorillonite nanoclay: The average particle size is 30-100 nanometers. Carbon Nanotubes: The average diameter is 1-10 nanometers.

6. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The crosslinking agent comprises the following ingredients: Aziridine compounds: one or more selected from 1,2-epoxy-3-(2-methoxyethoxy)propane and 1,2,7,8-diepoxyoctane; Isocyanate compound: one or more selected from hexamethylene diisocyanate and isophorone diisocyanate; Metal chelate: one or more selected from tetra-n-butyl titanate and tetra-n-butyl zirconate.

7. The waterproof and breathable laminating material for leather according to claim 1, characterized in that: The dispersant comprises the following ingredients: Polyphosphates: one or more selected from sodium hexametaphosphate and sodium tripolyphosphate; Acrylic polymer: one or more selected from sodium polyacrylate and polymethacrylic acid.

8. A method for preparing the waterproof and breathable laminating material for leather as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Raw material preparation: accurately weigh each component according to the weight percentage of the raw material for waterproof and breathable lamination of leather; Mixing and dispersion: add polyurethane resin, silicone modified acrylate copolymer, fluorocarbon surfactant and solvent into a high-speed disperser, and stir at a speed of 1000-1500 rpm for 30-60 minutes at a temperature of 25-35°C; Adding functional ingredients: under continuous stirring, slowly adding antifreeze agent, film-forming aid, plasticizer, functional nanofiller, crosslinking agent and dispersant in sequence, and continuing to stir for 15-30 minutes after each ingredient is added to obtain a mixture; Vacuum degassing: the mixture is transferred to a vacuum degassing device and treated at a pressure of -0.09 MPa to -0.1 MPa for 10-20 minutes to remove bubbles; Filtration and packaging: Use multi-stage filtration screens to remove large particles that are not fully dispersed, and then sterile packaging is performed to obtain the final product.

9. The method according to claim 8, characterized in that: During the mixing and dispersing, a high-speed disperser with heating and cooling functions is used to control the reaction temperature and keep the temperature fluctuation within ±2° C. during the stirring process.

10. The method according to claim 8, characterized in that: A pH adjuster is added to the added functional ingredients to maintain the pH value between 7.0 and 8.5.

Citation Information

Patent Citations

  • Preparation method of acrylate modified water-borne polyurethane emulsion for synthetic leather

    CN102408537A

  • Environmental-friendly waterproof and breathable clothing leather and preparation method thereof

    CN103835145A

  • Composite resin and preparation method thereof

    CN106221473A

  • Leather coating material and preparation method thereof

    CN112724813A

  • Water-based leather paint for automotive interior leather

    CN117165167A

Cited By

  • Fluoride-free waterproof agent with dynamic waterproof effect and preparation method thereof

    CN120536007A